World Class Reliability: Using Multiple Environment Overstress Tests to Make It Happen - Bhote, Keki R; Bhote, Adi K (American Management Association, 2004)
Companies following the Six Sigma process have seen their products' initial quality statistics soar, with defects all but eliminated. But how can companies make sure the quality lasts? One method is to subject products to exaggerated conditions that simulate the wear and tear of months, years, or a lifetime of use. Called Multiple Environment Overstress Tests (MEOST), these rigorous tests can expose potential design flaws, limitations of materials, and construction that normal quality inspections might miss. "World Class Reliability" presents a blueprint for creating and applying the MEOST methodology to products in almost any industry.